Figurative Language Aspects and Imagery in The Poetry Anthology Perahu Kertas By Sapardi Djoko Damono - Adiwijaya, Satria Nugraha; Supriyanto, Teguh; Indiatmoko, Bambang (Universitas Negeri Semarang, 2020)
This study aims to (1) describe the form and function of figurative language in the poetry anthology Perahu Kertas by Sapardi Djoko Damono, (2) describes the form and function of images used in the poetry anthology Perahu Kertas by Sapardi Djoko Damono, (3) describes the relationship of figurative language to images in the poetry anthology Perahu Kertas by Sapardi Djoko Damono. The analytical method used is descriptive semiotic analysis through heuristic and hermeneutic reading to reveal stylistic aspects and comparative analysis to describe the relationship between forms and functions of figurative language and imagery in the poetry anthology Perahu Kertas by Sapardi Djoko Damono.The results of the study based on data analysis showed (1) figurative language found, among others, was dominated by figure of speech and idioms with a limited number. The function of figure of speech is found, namely as the creation of aesthetic effects and comparison of meaning (2) the imagery data found is dominated by motion imagery with the function of reinforcing meaning to form imagery for the readers (3) there is a relationship between forms of figurative language and imagery in poetry anthology Perahu Kertas by Sapardi Djoko Damono